PROPOSED MARKETING STRATEGY ON BRAND AWARENESS FOR ETHISCROWD AS SHARIA EQUITY BASED CROWDFUNDING (The Indonesian Journal of Business Administration, 2019)
In order to compete with digital innovation in international level and technology industry in national level demand to have a breakthrough from local human resource to make innovation for better living of Indonesia. One of the rising online platforms in Indonesia is EthisCrowd categorized as sharia equity-based crowdfunding that is currently being the only Indonesia sharia equity crowdfunding that exist. In the business issue of EthisCrowd has a challenge of having people to increase invest and knowledge people in general invest little amount of money from total of annual invest potential in Indonesia. This challenge has to be formulized as strategy for EthisCrowd in order to archive gradual increasing performance each yea and sustain. The priority of increase invest with brand awareness to EthisCrowd as becoming the choice of investment platform. This research formulates on improving the implementation of EthisCrowd strategy.Keyword: Technology, FinTech, Sharia, Crowdfunding, Brand Awareness